2007
DOI: 10.1136/adc.2007.129098
|View full text |Cite
|
Sign up to set email alerts
|

Noise levels during nCPAP are flow-dependent but not device-dependent

Abstract: nCPAP drivers are valuable devices for neonatal care that may prevent primary mechanical ventilation or re-intubation, but generate a large amount of noise, often higher than occupational limits accepted for adult workers. Therefore, new devices must be designed to minimise this possible noxious exposure of premature infants to unacceptably high noise levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
4
22
1
1
Order By: Relevance
“…The recorded noise in our experiment represents the sum of sounds arising from this leakage as well as from gas flow and turbulences within the ventilator tubes. The correlation between gas flow and noise in this experimental setup was similar to that described in vivo by Karam et al [7] and Surenthiran et al [25] . Another aspect that has to be considered is the fact that in vivo bone conduction decreases the amount of noise transmitted to the inner ear.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The recorded noise in our experiment represents the sum of sounds arising from this leakage as well as from gas flow and turbulences within the ventilator tubes. The correlation between gas flow and noise in this experimental setup was similar to that described in vivo by Karam et al [7] and Surenthiran et al [25] . Another aspect that has to be considered is the fact that in vivo bone conduction decreases the amount of noise transmitted to the inner ear.…”
Section: Discussionsupporting
confidence: 68%
“…Among the main sources of noise in neonatal wards are the continuous positive airway pressure (CPAP) generators. A recent study by Karam et al [7] showed mean noise intensities of up to 120 decibels in an Aweighted scale [dB(A)] measured in the oral cavity of neonates on CPAP support. However, in this study, only jet CPAP generators were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing concern of excessive noise exposure in the NICU, noise levels generated by CPAP devices have been assessed in a number of studies previously [8,9,10]. This study is, to the best of our knowledge, the first to assess noise levels of HFNC devices.…”
Section: Discussionmentioning
confidence: 98%
“…Their study revealed that noise levels are much higher in the post-nasal space, in particular in babies on CPAP. A recent study by Karam et al [9] investigated noise levels of several CPAP devices by measuring in the oral cavity of preterm infants. The mean noise level was 88.6 dB(A) in their study, with two thirds of the measurements exceeding 90 dB(A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation